Multi-colour microscopic interferometry for optical metrology and imaging applications - Upputuri, Paul Kumar (2016)
Interferometry has been widely used for optical metrology and imaging applications because of their precision, reliability, and versatility. Although single-wavelength interferometery can provide high sensitivity and resolution, it has several drawbacks, namely, it fails to quantify large-discontinuities, large-deformations, and shape of unpolished surfaces. Multiple-wavelength techniques have been successfully used to overcome the drawbacks associated with single wavelength analysis. The use of colour CCD camera allows simultaneous acquisition of multiple interferograms. The advances in colour CCD cameras and image processing techniques have made the multi-colour interferometry a faster, simpler, and cost-effective tool for industrial applications. This article reviews the recent advances in multi-colour interferometric techniques and their demanding applications for characterization of micro-systems, non-destructive testing, and bio-imaging applications.